Penerapan Akuntansi Lingkungan Atas Pengelolaan Limbah Medis Pada Rumah Sakit Umum Daerah (RSUD) Kota Prabumulih - Restu Aini; Chairani Adelina; Meirani Betriana; Sri Suparni; Adelina, Chairani (LPPM Universitas Adiwangsa Jambi, 2025)
This study aims to analyze the implementataion of environmental accounting for medical waste management at the Regional General Hospital (RSUD) of Prabumulih City. The research method used is descriptive using a qualitative approach using secondary data by emphasizing the triangulation technique of combining observations, interviews and documentation to obtain data sources. The sampling technique of this study uses a non-probability technique by taking sample data using purposive sampling. The results of the study show that the Regional General Hospital (RSUD) of Prabumulih City has been in accordance with the category of environmental costs according to Hansen and Mowen's theory, namely prevention costs, detection costs, internal failure costs and external failure costs.